American Academy of Otolaryngology—Head and Neck Surgery Foundation Clinical Practice Guidelines: Allergic Rhinitis. (2nd September 2014) - Seidman, Michael D.; Gurgel, Richard K.; Lin, Sandra Y.; Schwartz, Seth R.
Abstract : Program Description: Allergic rhinitis is a worldwide health problem affecting 30 to 60 million people in the United States annually, including up to 30% of adults and as many as 40% of children. The multidisciplinary, AAO‐HNSF‐developed Clinical Practice Guideline: Allergic Rhinitis, will be presented. The evidence‐based recommendations are designed for clinicians involved in the diagnosis and management of patients with allergic rhinitis. Educational Objectives: (1) Properly diagnosis allergic rhinitis. (2) Differentiate between allergic and non‐allergic rhinitis. (3) Know when to perform allergy testing; and understand the role of immunotherapy (sublingual and subcutaneous).